Poor bone health in Duchenne muscular dystrophy: a multifactorial problem beyond corticosteroids and loss of ambulation - Hurley-Novatny, Amelia; Chang, David; Murakami, Katsuhiro; Wang, Ling; Li, Hongshuai (Frontiers in Endocrinology, 2024)
Duchenne muscular dystrophy (DMD) is a progressive, fatal muscle wasting disease caused by X-linked mutations in the dystrophin gene. Alongside the characteristic muscle weakness, patients face a myriad of skeletal complications, including osteoporosis/osteopenia, high susceptibility to vertebral and long bone fractures, fat embolism post-fracture, scoliosis, and growth retardation. Those skeletal abnormalities significantly compromise quality of life and are sometimes life-threatening. These issues were traditionally attributed to loss of ambulation and chronic corticosteroid use, but recent investigations have unveiled a more intricate etiology. Factors such as vitamin D deficiency, hormonal imbalances, systemic inflammation, myokine release from dystrophic muscle, and vascular dysfunction are emerging as significant contributors as well. This expanded understanding illuminates the multifaceted pathogenesis underlying skeletal issues in DMD. Present therapeutic options are limited and lack specificity. Advancements in understanding the pathophysiology of bone complications in DMD will offer promising avenues for novel treatment modalities. In this review, we summarize the current understanding of factors contributing to bone problems in DMD and delineate contemporary and prospective multidisciplinary therapeutic approaches.